Effect of the Outer Pipe on Reducing Direct Coupling of the Thin Borehole Radar Probe in Thick Water-Filled Borehole - Satoshi Ebihara; Raiki Masui; Koki Koyama; Yuki Tsujikawa; Yuto Nishida (Remote Sensing)
We propose an outer pipe to reduce a direct wave in a thin single-hole borehole radar probe in a thick water-filled borehole. The outer pipe replaces the medium, such as water inside the borehole, with low-permittivity materials, such as air and plastics. According to numerical calculations, the cylindrical water layer makes the direct wave from the transmitting loop antenna to the receiving one have significant power and narrow frequency bandwidth. This is caused by the low attenuation of the TE01 surface wave when there is a cylindrical water layer. The MoM analysis showed that wearing the outer pipe on the radar probe decreased the direct wave’s power more than the reflected wave from the subsurface objects, improving the detection of that reflected wave. We realized the radar system with the outer pipe by attaching the two acrylic pipes with different diameters. With this outer pie, we conducted field experiments to estimate the position of metal ore near the borehole in skarn with the loop antenna array type borehole radar. The direct wave having oscillation prevented the detection of the reflected wave from the sphalerite vein in the time domain without the outer pipe. However, attaching the outer pipe highlighted that reflected wave.